The Priority Needs of Parents' Satisfaction on An Art Course for Their Children: A Case of ABC Art Institute - Geng, Linhan; Preudhikulpradab, Sirichai; Barnes, John Arthur (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
This paper is a survey-based study with two research objectives, namely to identify the most important factors affecting parents' satisfaction, and to present a set of suggestions to improve parents' satisfaction. The research site was ABC Art Institution, Chengdu, China. The sample size in this study comprises the 35 respondents who filled out the questionnaire and eight informants who were interviewed. The tools used were a structured questionnaire and personal interview guide . Chronbach’s alpha and Item – Objective Congruence were used for reliability and validity test. Personal interviews used purposive sampling. Quantitative data was analyzed using descriptive statistics and Pearson correlation. Qualitative data was analyzed using content analysis . Key research results showed that learning contents (P< 0.001, r=0.574), skills development (P=0.028, r=0.371), learning process (P= 0.001, r=0.525), teacher and student interaction (P< .001, r=0.559), and tuition fee (P < .001, r=0.573) were significantly correlated with parents' satisfaction. Seven suggestions include: ABC Art Institution could offer more selection classes; Teachers should increase the guidance on children's imagination and create reasonable expectations for parents. Teachers must give feedback after class, interact with parents and children frequently, visit parents regularly, and externalize teaching effects regularly.